2014
DOI: 10.1111/1750-3841.12329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mild Temperature and Traditional Treatments on Residual Peroxidase Activity, Color, and Chlorophyll Content on Storage of Mate (Ilex paraguariensis) Tea

Abstract: The green coloring is the first characteristic in mate tea (chimarrão). Mate producers perform the sapeco process by rapidly passing the leaves through flames. It has been proven that this procedure leads to high energy consumption and also to excessive exposure of the raw material to heat. In this present work, the effect of sapeco on the inactivation of peroxidase, the color, and degradation of the chlorophyll in mate was evaluated by performing the sapeco procedure in a conveyor oven, without any direct con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The objective of the sapeco is to remove the superficial moisture and inactivate enzymes (peroxidases and polyphenoloxidases) which cause plant biomass oxidation, turning the leaves dark and the taste unpleasant (VALDUGA, 2002;NABECHIMA et al, 2014). This production system is currently mechanized; however, it follows the same principles practiced by the Indians who, manually, passed in a fast manner the raw material of stems with leaves over the flames of a wood fire, suitable for this purpose.…”
Section: Description Of the Installationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of the sapeco is to remove the superficial moisture and inactivate enzymes (peroxidases and polyphenoloxidases) which cause plant biomass oxidation, turning the leaves dark and the taste unpleasant (VALDUGA, 2002;NABECHIMA et al, 2014). This production system is currently mechanized; however, it follows the same principles practiced by the Indians who, manually, passed in a fast manner the raw material of stems with leaves over the flames of a wood fire, suitable for this purpose.…”
Section: Description Of the Installationsmentioning
confidence: 99%
“…The evaluations carried out indicated that the energy consumption in the sapeco operation exceeds that required for this operation. The literature has cited values of around 400 ºC as sufficient to inactivate enzymes and maintain the green color of the leaves (ESMELINDRO et al, 2002), while NABECHIMA et al (2014), indicated that the temperatures practiced should be sufficient for the inactivation of mate peroxidases (around 255 o C). The temperatures evaluated in the internal parts of the sapeco equipment and at the point where the leaves enter reach values of 540 to 560 ºC, which generates a loss of energy, besides a tendency toward a greater formation of polycyclic aromatic hydrocarbons, carcinogenic compounds generated by the burning of organic material at high temperatures.…”
Section: Evaluation Of Temperature Of Mate Processingmentioning
confidence: 99%
“…Besides that, chlorophyll degradation, and the consequent color loss of the leaves, is also associated to the plant's senescence (HORTENSTEINER, 2006). In this context, color has already been associated to plant degradation and age, for the Latin American plant Ilex paraguariensis, for example, in terms of food quality and storage (LEWINSKI et al, 2015;NABECHIMA et al, 2014).…”
Section: Imentioning
confidence: 99%
“…In rotary dyer, smoke of the fire makes direct contact with the raw material, while in the belt dryer, there is no such contact, resulting, less damage to the raw material Vieira et al 2010). The consumers priority of yerba-mate in Brazil is with a green color; however, in Chile and Uruguay they prefer the product with a yellow color (Valduga et al 2003), which is due to the degradation of chlorophyll (Nabechima et al 2014). To acquire this characteristic, milled yerbamate is stored for six months to one year, which provides color and flavor of a matured product (Isolabella et al 2010).…”
Section: Introductionmentioning
confidence: 99%